A Wirsing-type approach to some continued fraction expansion - Gabriela Ileana Sebe (International Journal of Mathematics and Mathematical Sciences)
Chan (2004) considered a certain continued fraction expansion and the corresponding Gauss-Kuzmin-Lévy problem. A Wirsing-type approach to the Perron-Frobenius operator of the associated transformation under its invariant measure allows us to obtain a near-optimal solution to this problem.